2019
DOI: 10.1177/1354068819850447
|View full text |Cite
|
Sign up to set email alerts
|

Investiture rules and formation of minority governments in European parliamentary democracies

Abstract: In parliamentary systems, political parties must often bargain with each other in order to form a government. Do parliamentary rules regulating government formation impact the type of government that is formed? Existing scholarship suggests that the need for an investiture vote -a requirement that a new government must face a parliamentary vote at some point during its formation -reduces the likelihood of a minority government. This paper suggests that while real-world investiture rules can vary across several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Minority governments emerge especially if parliaments are highly fragmented and polarized (Dodd 1976; Strøm 1990; Warwick 1998) and if institutional settings favor their formation (Strøm et al 1994). One common argument is that formal investiture votes minimize the chances for forming minority cabinets (e.g., Cheibub et al 2019; Strøm 1990). Bergman (1993) states that investiture votes only influence the formation of minority cabinets negatively if they require a majority vote in favor of the cabinet (i.e., positive parliamentarism) while negatively formulated or no requirements favor their formation.…”
Section: Explaining the Legislative Performance Of Minority Cabinetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Minority governments emerge especially if parliaments are highly fragmented and polarized (Dodd 1976; Strøm 1990; Warwick 1998) and if institutional settings favor their formation (Strøm et al 1994). One common argument is that formal investiture votes minimize the chances for forming minority cabinets (e.g., Cheibub et al 2019; Strøm 1990). Bergman (1993) states that investiture votes only influence the formation of minority cabinets negatively if they require a majority vote in favor of the cabinet (i.e., positive parliamentarism) while negatively formulated or no requirements favor their formation.…”
Section: Explaining the Legislative Performance Of Minority Cabinetsmentioning
confidence: 99%
“…But how do minority cabinets avoid policy defeat and stay in control over the legislative agenda? Despite the recently raising interest in minority cabinets by political scientists (Anghel and Thürk 2021; Cheibub et al 2019; Ganghof et al 2019; Kefford and Weeks 2020; Klüver and Zubek 2018; König and Lin 2020; Matthieß 2018; Potrafke 2019), there is still little comparative research about the legislative activity of minority governments. Minority cabinets have become a more common phenomenon worldwide due to the decline in vote (and seat) shares of parties as well as the growing fractionalization and polarization of party systems.…”
Section: Introductionmentioning
confidence: 99%
“…Spain's constitution is somewhat exceptional in this regard. It requires an absolute majority for a constructive no-confidence vote but only a simple majority in the second round of an investiture vote (Ajenjo 2015;Cheibub et al 2021). Even in this case, though, the constructive no-confidence vote may work against (single-party) minority cabinets.…”
Section: Dealing With Complexitymentioning
confidence: 99%
“…Sieberer (2015) has shown that cabinet selection and removal rules are correlated in this way. Yet when the cabinet has to be voted into office by a majority in parliament, or at least when this majority must be absolute, the formation of minority cabinets becomes more difficult (Bergman, 1993;Cheibub, Martin, & Rasch, 2019). When simple majorities are ultimately sufficient in an investiture vote, the formation of (singleparty) minority cabinets becomes relatively easier, Spain being a case in point (Field, 2016).…”
Section: Optimizing Executive-legislative Relationsmentioning
confidence: 99%